2004
DOI: 10.1063/1.1833564
|View full text |Cite
|
Sign up to set email alerts
|

Tunable optical switch using magnetic fluids

Abstract: With a tunable refractive index, magnetic fluid can be applied to the development of adjustable optical devices. In this work, a magnetic-fluid-based optical switch is designed and characterized. The optical switch is formed by sealing magnetic fluid between two glass prisms. When a light is incident to one side of one of the prisms, a reflected light from the magnetic fluid film comes out from the same prism, whereas a transmitted light through the film emits from the other prism. It was found that the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(51 citation statements)
references
References 8 publications
0
48
0
3
Order By: Relevance
“…As one of the representative magnetic materials, magnetite (Fe 3 O 4 ) always attracts extensive research interest in materials science due to its low producing cost, environmental benignity, interesting magnetic behaviors, and widely potential applications in drug-delivery, gas sensors, magnetic filters, electrode materials, magnetic storage media, and microwave-absorbing materials [13][14][15][16][17][18][19][20]. Many methods have been developed for the preparation of magnetite nanoparticles, including coprecipitation of Fe 2+ and Fe 3+ ions in alkaline solutions [21], ultrasound assisted preparation [22], thermal decomposition of Fe(acac) 3 precursor [23], polyol route [24], hydrothermal process [25,26] and solvothermal technique [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the representative magnetic materials, magnetite (Fe 3 O 4 ) always attracts extensive research interest in materials science due to its low producing cost, environmental benignity, interesting magnetic behaviors, and widely potential applications in drug-delivery, gas sensors, magnetic filters, electrode materials, magnetic storage media, and microwave-absorbing materials [13][14][15][16][17][18][19][20]. Many methods have been developed for the preparation of magnetite nanoparticles, including coprecipitation of Fe 2+ and Fe 3+ ions in alkaline solutions [21], ultrasound assisted preparation [22], thermal decomposition of Fe(acac) 3 precursor [23], polyol route [24], hydrothermal process [25,26] and solvothermal technique [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the refractive index of the MF will increase with the strength of the magnetic field. So the index difference between the fiber and the MF will reduce, and then more evanescent field is guided in the MF, 25 which can be seen in Fig. 4.…”
Section: Resultsmentioning
confidence: 91%
“…The amplitude of S z in the guiding layer is enhanced by 68 times than that in the air before coupling into the DMCW structure. As was pointed out by Deng et al (2008), Horng et al (2004), Dai et al (2010), the clustering of magnetic nanoparticles will be resolved at large power densities and resulting in a rapid agglomeration when an external field is applied. However, as will be clarified later, apart from high energy density, large-scale optical trapping effect inside the guiding layer may be the primary reason for the rapid agglomeration of nanoparticles.…”
Section: Theory and Discussionmentioning
confidence: 94%
“…However, the mechanisms governing the dynamics are still ambiguous, which cause the research on the response time of chain formation play an important role on the further application. A number of reports have pointed out that the agglomeration rate of magnetic nanoparticles is usually in second scale (Deng et al 2008;Horng et al 2004;Dai et al 2010) or even in minute scale (Li et al 2007(Li et al , 2002. In addition, it is also demonstrated that a finite retardation exists between the switch on/off of the external field and the variation of the transmission through the ferrofluid films, and this corresponding retarding time ranges from several to tens of milliseconds, depending on the field strength .…”
Section: Introductionmentioning
confidence: 97%